Transition To A Green Economy In The Context Of Selected European And Global Requirements For Sustainable Development - Wysokińska, Zofia (Comparative Economic Research. Central and Eastern Europe, 2014)
The aim of the paper is to present selected aspects of sustainable development related to environmental protection and the creation of a green economy, with special reference to the global and European context for the development of an environmentally friendly goods and services market, taking into account the cases of Central and Eastern European countries. One of the most important elements of the strategy to promote clean economic growth and foster the transition to a more sustainable and greener economy is the energy sector, where the aim is to reduce greenhouse gas emissions and sulfur oxides and support the development of renewable energy sources. Some of the achieved results in this area are presented in this paper.